2016
DOI: 10.1007/s10457-016-9891-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of selected indigenous dryland agroforestry tree species to salinity and implications for soil fertility management

Abstract: Salt tolerant plants are known to remove excess soluble salts from the soil and thus may be used in land reclamation.We studied the responses of the trees, Balinites aegyptiaca L. (Zygophyllaceae), as well as the Fabaceae, Acacia tortilis (Forssk) Hayne, and Tamarindus indica L. to salinity. Three experiments were conducted on: germination, in the laboratory; seedling performance in a lath house; and, the impact of the tree species on soil productivity in the field in Afar regional state along the Awash river,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Jimenez-Casas and Zwiazek (2014) observed that Pinus leiophylla's stem diameter growth decreased with increasing NaCl concentration. Also, the RCD of a native dryland agroforestry tree species, Acacia tortilis, was severely impacted by salinity (Seid et al 2016). For Senegalia senegal, Vachellia seyal, and Prosopis juliflora, Fall et al (2016) observed that salinity reduced significantly the RCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jimenez-Casas and Zwiazek (2014) observed that Pinus leiophylla's stem diameter growth decreased with increasing NaCl concentration. Also, the RCD of a native dryland agroforestry tree species, Acacia tortilis, was severely impacted by salinity (Seid et al 2016). For Senegalia senegal, Vachellia seyal, and Prosopis juliflora, Fall et al (2016) observed that salinity reduced significantly the RCD.…”
Section: Discussionmentioning
confidence: 99%
“…For Senegalia senegal, Vachellia seyal, and Prosopis juliflora, Fall et al (2016) observed that salinity reduced significantly the RCD. In contrast, salinity had no effect on the RCD of Balanites aegyptiaca (Seid et al 2016). In addition, the greenhouse experiment of Duan (2015) demonstrated the effectiveness of N fertilization in improving the growth of seedlings in a saline growth media, resulting in improved RCD growth for both Pinus contorta and Picea glauca seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Tamarindus indica L. (hereafter T. indica) is one of the multipurpose trees in sub-Saharan zones and traditionally builds resilience to the farming systems [ 7 , 8 ]. Beyond maintaining ecological sustainability [ 9 , 10 ], T. indica is an indigenous semi-evergreen tree species of the Fabaceae family, widely distributed across the sub- and semi-arid tropics [ 7 , 11 ] and is preferred for its wild edible fruit and timber [ 7 ], fodder for animals [ 12 ], medicinal value [ [13] , [14] , [15] , [16] , [17] , [18] ], food [ 18 , 19 ] and improve soil fertility [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%